2015
DOI: 10.1165/rcmb.2014-0333oc
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Epithelial Signal Transducer and Activator of Transcription 1 Activation by Extracts of Aspergillus fumigatus

Abstract: Aspergillus fumigatus (AF) is often pathogenic in immune-deficient individuals and can cause life-threatening infections such as invasive aspergillosis. The pulmonary epithelial response to AF infection and the signaling pathways associated with it have not been completely studied. BEAS-2B cells or primary human bronchial epithelial cells were exposed to extracts of AF and challenged with IFN-b or the Toll-like receptor 3 agonist double-stranded RNA (dsRNA). Cytokine release (B-cell activating factor of the TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 48 publications
3
21
0
Order By: Relevance
“…Recently, we have reported a rapid dephosphorylation of IFN-β-induced phospho-STAT1 triggered by AF extract and have confirmed this in the present study (Supplemental Fig. 2A, B) (6). Since the apparent dephosphorylation of IRF-3 shown in Fig.…”
Section: Suppression Of Poly I:c-induced Cxcl10 By Af Extract Was Medsupporting
confidence: 91%
See 4 more Smart Citations
“…Recently, we have reported a rapid dephosphorylation of IFN-β-induced phospho-STAT1 triggered by AF extract and have confirmed this in the present study (Supplemental Fig. 2A, B) (6). Since the apparent dephosphorylation of IRF-3 shown in Fig.…”
Section: Suppression Of Poly I:c-induced Cxcl10 By Af Extract Was Medsupporting
confidence: 91%
“…Previous studies by our laboratory and others have shown that extracts of Aspergillus fumigatus suppress Page 13 of 44 activation of epithelial cells by either IFN or by the TLR3 agonist poly I:C (6,18,28,29). In the present study, we show that AF extract also suppressed the HRV16-induced innate immune response in fully differentiated NHBE cells using an air liquid interface culture system (Fig.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations